Asymptomatic coronavirus disease followed by symptomatic reinfection in a patient with monoclonal gammopathy of undetermined significance: A case report (Indian Journal of Case Reports, 2021)
Coronavirus disease (COVID-19) pandemic has been present for over a year and has been seen to behave unpredictably in different people especially those with other underlying health conditions. Monoclonal Gammopathy of Undetermined Significance (MGUS) is a rare condition that can alter immune responses. There are few case reports of COVID in people with MGUS and most of these are in elderly people often with associated comorbidities. The mutual impact of COVID and MGUS in younger people (<50 years) has been far less explored, and therefore, this case report would add to such data. Although there is no conclusive evidence to suggest that MGUS increases predisposition or significantly impacts the clinical course and outcomes of COVID-19, it can have some bearing on serological assessment in both COVID infected or vaccinated individuals.